2021
DOI: 10.1186/s13102-021-00332-x
|View full text |Cite
|
Sign up to set email alerts
|

The effect of aerobic exercise on interoception and cognitive function in healthy university students: a non-randomized controlled trial

Abstract: Background Interoception refers to the body’s physiological responses that occur in response to emotions. This phenomenon influences decision-making, an important cognitive ability that affects the maintenance of an exercise routine. However, it is controversial whether interoception is a reliable measure of an individual’s traits or their response to emotion. Given this evidence, we hypothesized that performing an exercise with positive feelings could improve interoception and that the rationa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
0
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 50 publications
1
0
0
Order By: Relevance
“…To further the idea that exercise has a positive impact on auditory memory, a 2021 study was led by Yusaku Amaya, member of the Department of Psychosomatic and General Internal Medicine for Kansai Medical University. An auditory test confirmed that exercise improved test scores, but not in a significant way (Amaya et al, 2021). This evidence, and those from other sources, helped direct my observations to the hypothesis that dance would better enhance visual memory.…”
Section: Literature Reviewsupporting
confidence: 64%
“…To further the idea that exercise has a positive impact on auditory memory, a 2021 study was led by Yusaku Amaya, member of the Department of Psychosomatic and General Internal Medicine for Kansai Medical University. An auditory test confirmed that exercise improved test scores, but not in a significant way (Amaya et al, 2021). This evidence, and those from other sources, helped direct my observations to the hypothesis that dance would better enhance visual memory.…”
Section: Literature Reviewsupporting
confidence: 64%
“…Research indicates that exercise enhances cognition, as the basal ganglia control fine motor movements during physical activity, forming a feedback loop with the prefrontal cortex that impacts higher brain functions, such as learning or cognition ( 18 ). A meta-analysis confirms that aerobic exercise generally improves cognitive function, irrespective of the initial cognitive state ( 29 ).…”
Section: Discussionmentioning
confidence: 99%
“…However, Tang et al reported that neither high- nor low-intensity aerobic exercise improved cognitive and executive functions in patients with post-stroke cognitive impairment ( 28 ). Amaya et al ( 18 ) emphasized the importance of exercise enjoyment for sustained engagement and noted that moderate-intensity aerobic exercise increased enjoyment, whereas high-intensity exercise affected decision-making. Studies have shown that both moderate and high-intensity aerobic exercises are linked to better cognitive improvements compared with low-intensity exercise ( 17 ).…”
Section: Discussionmentioning
confidence: 99%